PENGARUH KUALITAS PELAYANAN DAN KEPUASAN TERHADAP KEPERCAYAAN NASABAH PT. PEGADAIAN CABANG PONTIANAK - B31111135, Alexander Jorgi (Jurnal Manajemen Update, 2016)
The study is done with a view to analyze influence the quality of service, customer satisfaction with confidence PT. Pegadaian Cabang Pontianak and analyze influence the quality of service for customer satisfaction. The population of the research is all customers PT. Pegadaian Cabang Pontianak. Sample withdrawal used technique purposive sampling. The get as many as 100 respondents. Data collection method done with the questionnaire. The method of analysis research conducted it uses path analysis with a significantly by 5 %. The result showed that the partial quality of services and satisfaction influential positive and significant directly to trust customers. And quality of services influential positive and significantly to customer satisfaction. The conclusion of research is when quality of services and satisfaction applied increased, then trust customers is increased. Advice to researchers next to stay consider variabel quality of services and satisfaction as factor forming trust customers. In addition to develop a result of research is expected to increase variable another as commitment. Keywords: the quality of service, satisfaction, trust and PT. Pegadaian Cabang Pontianak.